2019
DOI: 10.1111/aor.13534
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of HBOC‐201 in ex situ gradual rewarming kidney perfusion in a rat model

Abstract: Gradual rewarming from hypothermic to normothermic is a novel perfusion modality with superior outcome to sudden rewarming to normothermic. However, the identification of an oxygen carrier that could function at a temperature range from 4 to 7°C or whether it is necessary to use oxygen carrier during kidney rewarming, remains unresolved. This study was designed to test the use of a hemoglobin‐based oxygen carrier (HBOC) during gradual kidney rewarming as an alternative to simple dissolved oxygen. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Interestingly, Hemopure (HBOC-201) has been approved by the South African drug council for the treatment of anemia. Moreover, this product is allowed to be used in United States in qualified patients to treat severe life-threatening anemia under the FDA’s expanded compassionate use access program [ 20 , 26 , 27 , 28 , 29 ]. Additionally, one randomized, multicenter trial investigation of HBOC-201 in non-cardiac surgery patients indicated that its use reduced RBC transfusions in 43% of patients without notable differences in mortality and serious adverse events, though there was a notable increase in the associated non-serious events (i.e., hypertension and fever) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Hemopure (HBOC-201) has been approved by the South African drug council for the treatment of anemia. Moreover, this product is allowed to be used in United States in qualified patients to treat severe life-threatening anemia under the FDA’s expanded compassionate use access program [ 20 , 26 , 27 , 28 , 29 ]. Additionally, one randomized, multicenter trial investigation of HBOC-201 in non-cardiac surgery patients indicated that its use reduced RBC transfusions in 43% of patients without notable differences in mortality and serious adverse events, though there was a notable increase in the associated non-serious events (i.e., hypertension and fever) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBOC-201 has been evaluated in ex vivo perfused porcine kidney, and demonstrated similar renal function and equivalent tissue oxygen saturation compared to a blood-treated kidney [16]. This molecule has also been evaluated in gradual rewarming protocols (see below), where it demonstrated the ability to withstand a wide range of temperatures [17].…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…Probably because of early disappointing results with perfluorocarbons, there has been no attempt to use these in extremity perfusion studies. However, HBOCs with the ability to function in a wide range of temperatures, from hypothermic to normothermic, seem to be an option for ex vivo perfusion . Hemoglobin‐based oxygen carrier 201 (HBOC‐201) is an ultra‐purified bovine hemoglobin derivative polymerized with glutaraldehyde; its low P 50 results in lower O 2 affinity than native hemoglobin .…”
Section: Perfusatementioning
confidence: 99%
“…However, HBOCs with the ability to function in a wide range of temperatures, from hypothermic to normothermic, seem to be an option for ex vivo perfusion. 40 Hemoglobin-based oxygen carrier 201 (HBOC-201) is an ultra-purified bovine hemoglobin derivative polymerized with glutaraldehyde; its low P 50 results in lower O 2 affinity than native hemoglobin. 41 In 2016, Schweizer et al 42 used an HBOC during subnormothermic MP (21°C) for a 14-hour flap perfusion before heterotopic transplantation.…”
Section: Perfusatementioning
confidence: 99%